FINANCIAL MANAGEMENT IN STRENGTHENING EDUCATIONAL GOVERNANCE AT MUHAMMADIYAH UNIVERSITY OF TANGERANG - Ardiyanti, Anita; Hadiwijaya, Dudung; Murniadi, Murniadi; Sutarman, Sutarman (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study examines the role of financial management in strengthening educational governance at the Muhammadiyah University of Tangerang. Effective financial management is a crucial component of good university governance, as it ensures transparency, accountability, efficiency, and sustainability in the management of educational resources. Purpose: This research aims to analyze financial planning, implementation, supervision, and accountability mechanisms in supporting institutional governance and improving educational quality. Method: Using a qualitative approach, data were collected through document analysis, interviews, and observations involving university leaders and financial management units. Result: The findings indicate that structured financial planning, transparent budgeting systems, and effective internal control mechanisms contribute significantly to strengthening educational governance at the Muhammadiyah University of Tangerang. Moreover, alignment between financial policies and institutional strategic goals enhances organizational performance and stakeholder trust. Conclusion: This study concludes that sound financial management practices play a vital role in reinforcing good governance in higher education institutions and supporting the achievement of sustainable educational development.